KAJIAN ONTOLOGIS LEMBAGA MEDIASI DI PENGADILAN - Rahadi Wasi Bintoro (Yuridika, 2016)
The implementation of mediation in court still seems formalistic. This condition makes the process of a civil case proceed to Supreme Court. Supreme Court Regulation No.1 of 2008 aimsto stream line the mediation institute incourt. However, in practice the Supreme Court Regulation No. 1 of 2008 was no different with Article 130 HIR, it even contrary to mediatio nontology and simple, fast and in expensive Justice Prinsiple. Mediation in court is institutionalization and empowerment of peace (court connected mediation) with the philosophical foundation is Pancasila which is the basis of our country especially the fourth precepts "People led by Wisdom Wisdom in Consultation / Representation". The fourth precepts of the Pancasila include, among others, the efforts to resolve disputes, conflicts or cases through deliberations to reach consensus encompassed by the spirit of kinship. This means that any dispute, conflict or matter should be resolved through negotiation or peace procedures among the disputing parties to obtain a collective agreement.